2007
DOI: 10.1111/j.1365-313x.2006.02983.x
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA156/157 recognition element in the 3′ UTR of the Arabidopsis SBP box gene SPL3 prevents early flowering by translational inhibition in seedlings

Abstract: Summary miRNAs are a class of versatile small RNAs that control gene expression post-transcriptionally, governing many facets of plant cell functions. They interact with their target mRNA at a site of sequence complementarity and modulate their expression levels. Here, we provide evidence, based on transient assays and stable transgenic lines, that the 3¢ UTR of the Arabidopsis SBP box gene SPL3 contains a functional miRNAresponsive element (MRE) that is complementary to miR156 and miRNA157. Seedlings of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
472
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(495 citation statements)
references
References 51 publications
18
472
0
5
Order By: Relevance
“…aqcmiR156 is predicted to regulate five SQUAMOSA PROMOTER BINDING PROTEINLike (SBP) genes and one homolog of Growth Regulating Factor 2 (Table 3). miR156 regulation of the above targets has been shown to play important developmental roles in other plants species, including regulating plastochron length (Wang et al, 2008), organ size (Wang et al, 2008), cell number (Usami et al, 2009, and phase change (Gandikota et al, 2007). Guo et al (2008) reported that the miR156 binding site is highly conserved in land plant SBP genes so our Aquilegia predictions are consistent with these obervations (Guo et al, 2008).…”
Section: Mir156/529mentioning
confidence: 99%
“…aqcmiR156 is predicted to regulate five SQUAMOSA PROMOTER BINDING PROTEINLike (SBP) genes and one homolog of Growth Regulating Factor 2 (Table 3). miR156 regulation of the above targets has been shown to play important developmental roles in other plants species, including regulating plastochron length (Wang et al, 2008), organ size (Wang et al, 2008), cell number (Usami et al, 2009, and phase change (Gandikota et al, 2007). Guo et al (2008) reported that the miR156 binding site is highly conserved in land plant SBP genes so our Aquilegia predictions are consistent with these obervations (Guo et al, 2008).…”
Section: Mir156/529mentioning
confidence: 99%
“…It is highly conserved in the plant kingdom and has been identified in 45 different plant species [12]. miR156 has been demonstrated to target SPL genes, which are plant specific transcription factors containing an SBP box [6,[13][14][15]. Recently, evolution of miRNA families with multiple members (such as miR156, miR169 and miR395) has been investigated in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…We found significant variation with flow rate, suggesting a mass transfer limitation (data not shown). Varying concentrations of recombinant protein (5,10,15,20,25,30, and 50 nM) were injected at the higher flow rate (75 µL/min). The SPR response data were then fit to various models using BIAevaluation 3.0 software (Biacore).…”
Section: Identification Of a Consensus Binding Site For The Atspl14 Smentioning
confidence: 99%
“…In all cases, SBP domain proteins have been implicated in various aspects of plant growth and development, including metal sensing in algae and directing development of leaves, embryos, and floral organs in higher plants (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Some of these SBP do-main proteins may also be posttranscriptionally regulated by noncoding microRNAs to control their spatial and temporal expression (23)(24)(25). Despite the obvious importance of these proteins, the specific genes targeted by individual SBP domain family members and the molecular consequences of their actions are largely unknown.…”
mentioning
confidence: 99%